Enhancing Students' Speaking Skills Through Storytelling Methods and Image Media at PAUD Uma Kandung Tambarangan - Feka, Frida (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
This research was conducted to improve children's speaking skills through the storytelling method and card media. To try to give encouragement in one way so that children